2012
DOI: 10.1016/j.intcom.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Embodiment and telepresence: Toward a comprehensive theoretical framework

Abstract: a b s t r a c tWhat explains the experience of ''being there'' in a simulated or mediated environment? In recent years, research has pointed to various technological and psychological factors deemed important in eliciting this so-called experience of telepresence, including interactivity, sensory-motor integration, media transparency, and distal attribution. However, few theories exist that can combine these findings in a coherent framework. In the present paper, we formulate such a theoretical framework. We w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 68 publications
1
69
0
3
Order By: Relevance
“…Haans & IJsselsteijn (2012) consider third-order embodiment to be necessary for presence, but this is only the case when there is a conflict between the mediated view of the body and the body image of the perceiver. When this happens, the relevant mediating body extension becomes an object in the world rather than an integral part of the self.…”
Section: Distributed Embodiment: That's Me Over There!mentioning
confidence: 99%
See 1 more Smart Citation
“…Haans & IJsselsteijn (2012) consider third-order embodiment to be necessary for presence, but this is only the case when there is a conflict between the mediated view of the body and the body image of the perceiver. When this happens, the relevant mediating body extension becomes an object in the world rather than an integral part of the self.…”
Section: Distributed Embodiment: That's Me Over There!mentioning
confidence: 99%
“…Unless we can act in a world (whether physical, virtual, or a mixture of both) we will not feel ourselves to be greatly present in it. When we act in mediated worlds, we may interact through different degrees and forms of embodiment and this has implications for the extent to which we can potentially feel present in the world (Haans & IJsselsteijn, 2012). We suggest that in principle we can understand when and how some technologies become embodied and others do not by examining the strength and nature of our feelings of presence in the world the technology creates or mediates.…”
Section: Introduction To Chapter 2: Presence and Three Categories Of mentioning
confidence: 99%
“…As pointed out in the Introduction section, the most important of these items for this study are selfawareness, sense of agency and sense of body ownership, because they are closely related to the sense of presence experienced inside the virtual environment. The sense of body ownership allows you to discriminate your individual's own body and perceptions; forming the "body schema" which covers the dynamic distributed network of procedures aimed to guide your behavior (Haans and IJsselsteijn, 2012). The results of this study showed a parametric increase in the activation of the right insula according to the sense of presence experience in the conditions.…”
Section: Discussion Of the Resultsmentioning
confidence: 66%
“…So the fact that the subjects are not familiarized with the environments should not prevent the sense of presence. Moreover, the central nervous system is capable to incorporate the new tools and technological artifacts that are used in the virtual experiences to its representation of the body schema, integrating them in a functional unity with our biological limbs and sensory receptors (Haans and IJsselsteijn, 2012), helping the interface transparency or "disappearance of mediation" (Riva et al, 2003).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation